Earnings Management and Possible Consequences of Its Misuse - Boris KOLLAR; Anna SIEKELOVA (Communications of International Proceedings, 2021)
The paper is focused on earnings management and possible consequences of its misuse. Earnings management may result into possible fraudulent behavior in commercial companies. The main focus among these possible consequences, is put on economic crimes on the global and also local scale in the form of Slovak republic. The motives behind earnings management usage is adjustment of earnings to the needs of the company. The submitted paper also discusses possible prevention of this unwanted outcome. It also deals with the concept of creative accounting and how it is indicated. Earnings management is often considered to be a subset of creative accounting itself and therefore, there is strong connection between these two topics. Improper use of them may cause and increase economic instability and sanctions by global and national regulators. The discussion contains the overview of the presented topics and also the most famous misuse of earnings management from global perspective. At last, but not least, the paper highlights the importance of knowledge for users of this techniques and the importance of information they provide to the company.
Keywords: Earnings management; Creative accounting; Economic impact; Comparison; Prevention.